Peningkatan Hasil Belajar Siswa Melalui Program Refleksi Mingguan pada Guru MTsS Monisa Kabupaten Aceh Timur - Yahya, Muhammad; Jamali (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
Reflection is a process of reviewing the implementation of learning carried out by educators. Implemented critically and continuously to obtain descriptions, results of analysis and evaluation of a lesson carried out by educators, the implementation of the review is inseparable from the objectives of achieving learning outcomes. This madrasah action research was carried out in two cycles of four meetings consisting of 1) planning, 2) implementation, 3) observation and 4) reflection which aims to improve student learning outcomes through a weekly reflection program for MTsS Monisa teachers, East Aceh District, odd semesters of the school year. 2019/2022. In collecting this data, researchers used observation, assessment and questionnaire techniques. From the results of the reflection program research, it was obtained that in cycle I got a score of 3 (good enough) while in cycle II it increased with a score of 4 (good). It can be concluded that the weekly reflection program can improve student learning outcomes and this program is an alternative for teachers who teach in class